Pd(II)-catalyzed ortho arylation of 2-arylbenzothiazoles with aryl iodides via benzothiazole-directed C–H activation - Ding, Qiuping (Elsevier Sequoia, 2012)
A novel and efficient method for the arylation of 2-arylbenzothiazoles is described via C–H activation. The desired C(Ar)–C(Ar) bond formation proceeded efficiently with good functional-group tolerance and high regioselectivity. Proposed mechanism for the arylation of 2-arylbenzothiazole is depicted.